The Effect of Planting Distance and Depth of Water Puddle to Damage Intensity by Rice Yellow Stem Borer (Scirpophaga incertulas Walker) (Lepidoptera: Crambidae) in Relation to Microclimate Change - Ulfah Nuzulullia; Edhi Martono; Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2019)
The rice yellow stemborer (Scirpophaga incertulas) is one of main pests on rice which may attack at all growth stages. The weather was considered one of influencing factors against its infestation. Therefore, this research was conducted to recognize microclimate factors affecting the infestation of S. incertulas. The experiment was carried out in Institute for Pest Forecasting, Jatisari Karawang from January-April 2017. The investigation was arranged in Factorial of Blocked Randomized Design with four repetitions and  combinations of treatment factors, i.e. planting distance (conventional and jajar legowo 2 : 1) and depth of puddle (5 cm, 0 cm, and intermittent). The observation was performed from one to 12 weeks after planting. At the same time, three weather factors (temperature, relative humidity and rainfall) were observed in four West Java regencies i.e. in Bekasi, Karawang, Subang and Indramayu. The results showed that the conventional and the jajar legowo schemes are influenced by the micro air temperature.  Both planting distance and depth of water puddle treatment were influenced by the micro air temperature. Microclimate factors which influenced the intensity of infestation were air temperature, humidity, water temperature, and light intensity. The weather factor showing effects  in Bekasi, Karawang, and Indramayu was rainfall. However, the three weather factors did not affect on the acreage of pest infestation in Subang.